Study of Far Infrared Nebula at Declination +53° (J2000) In Iras Map - Gautam, Sabin; Gautam, Suman; Poudel, Parashu Ram (Himalayan Physics, 2017)
In this present work we studied the flux density variation, calculate temperature, dust mass and finally Jean’s mass of structure using data reduction software ALADIN2.5. Our aim was to test whether this region is star forming or not. Sky view observatory was used for the search of isolated nebular structure in the far infrared (100 μm and 60 μm) in IRAS (Infrared Astronomical Satellite) catalogue. Stellarium software was used to find coordinate of the structure. A far infrared dust structure (about ~ 11.99 × 3.14 pc.) at Right Ascension (J2000):01h 51m 56.02s Declination (J2000): +53deg 27m 39.0s found at the distance of about 550 pc. The dust color temperature was found to lie in the range 18.02 K to 39.56 K. An offset of about 21 K suggests that the structure is not independently evolved, discrete source may play significant role in structure formation mechanisms. The study of flux variation along major and minor axis of structure showed that mass is concentrate at the center of structure. The total mass of the gas structure was found to be about 1.1432× 1031Kg. The Jeans mass was found to be 1.17 x 1033Kg, more than that of the total mass of the structure, suggest no clue of star formation. The Himalayan Physics Vol. 6 & 7, April 2017 (76-79)